Improving fitness professionals' awareness and understanding of eating disorder symptoms: Effects of a brief intervention - Boulet, S.; Blaszczynski, A.; Miskovic-Wheatley, J.; Pickering, D.; Maguire, S. (Journal of Science and Medicine in Sport Plus, 2023)
Objectives Eating disorders (EDs) are complex, potentially life-threatening mental illnesses associated with low detection in health settings and low treatment rates. Compulsive exercise is a common ED feature, with symptoms likely to manifest in fitness settings. Fitness professionals are ideally placed to identify ED indicators among clients, to encourage help-seeking, and to offer referrals to specialist treatment services. This study aimed to investigate whether existing industry guidelines in Australia (i.e., "Eating Disorders: Recommendations for the Fitness Industry") help to improve fitness professionals` awareness and understanding of ED symptoms and appropriate interventions when detected among clients.